Role of Administrative Oversight in Improving Principals’ Management Performance in Southern-Hebron Public Schools from their View - Bhais, Jamal Mohammed (Journal of Educational and Psychological Sciences, 2022)
The present study, whereby the descriptive analytical methodology is applied, aims at identifying the role of administrative oversight in improving principals’ management performance in Southern-Hebron public schools with due respects to variants of gender, administrative experience and that of directorate. For the sake of the study, the researcher targeted a population of (271) principals of who (180) participants made a sample of (180) principals within the schools run by the directorates of Southern-Hebron. For data analysis, the (spss) test was applied. Results show that the whole fields score (3.67-high). In that regard, (i) the role of administrative oversight in monitoring ’s files and records scores (3.61) on average and there is no significance differences shown at alpha (α≤0.05) regarded to variants of gender, experience, qualification and the district. (ii) teachers monitoring shows higher as (4.16), (iii) an average of (3.06) goes to the role of oversight in improving administrative and financial performance, whereas, the role of oversight in assessment scores (3.85) on average. In consequence, the researcher recommends the principals to participate in constructing the oversight system within their directorates.